2012
DOI: 10.1517/17425247.2012.642362
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate: a detailed review on drug delivery and clinical aspects

Abstract: Therapeutic drug monitoring of MTX is crucial to attain a good efficacy. In spite of the advantages of multiparticulate, prodrug and drug conjugates, clinical applications of such formulations of MTX are still under infancy. These drug delivery systems require the special attention of medical experts for its wider clinical usage, and pharmaceutical experts for its scale-up. The combination of MTX with other antineoplastic and immunosuppressants should also be subjected to clinical trials, such as the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(141 citation statements)
references
References 117 publications
1
133
0
3
Order By: Relevance
“…Being able to enter a cell via pinocytosis, a carrier also would allow overcoming the resistance of tumor cells caused by impaired transmembrane transport. Indeed, in the last decade, a burst of research has been conducted on MTX-bearing drug delivery systems, 3,4 including…”
Section: Introductionmentioning
confidence: 99%
“…Being able to enter a cell via pinocytosis, a carrier also would allow overcoming the resistance of tumor cells caused by impaired transmembrane transport. Indeed, in the last decade, a burst of research has been conducted on MTX-bearing drug delivery systems, 3,4 including…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, long-term use and high-dose Mtx given by systematic administration have been associated with drug resistance and adverse side effects. 13,14 Therefore, it is desirable to develop a system that can deliver Mtx selectively to target tissues and to release the encapsulated Mtx within a short time. 15 In order to deliver encapsulated drug to target tissues efficiently, efforts have been devoted to the development of intelligent delivery systems that respond to specific stimuli, such as pH level, temperature, and redox potential.…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate is a drug used widely for the treatment of different types of cancers and autoimmune diseases like rheumatoid arthritis [22]. Tripathi et al, [23] have reported that it has been used as a first line drug in many autoimmune diseases pemphigus, myasthenia gravis, uveitis, chronic active hepatitis.…”
Section: Discussionmentioning
confidence: 99%